2007
DOI: 10.1002/lt.21268
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation using suboptimal grafts: Impact of donor harvesting technique

Abstract: In recent years, an increasing number of suboptimal grafts has been used to reduce the gap between the supply and demand of organs for liver transplantation (LT). In this randomized prospective study, we tested the impact of donor harvesting technique on the posttransplantation outcome of suboptimal donor livers. A modified double perfusion (MDP) technique (aortic and portal cooling with tourniquet clamping of splenomesenteric vein inflow) was compared with the single aortic perfusion (SAP) technique. Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…Elderly grafts are more susceptible to ischemia/reperfusion injury because of hemodynamic instability. 13 Shorter cold ischemia time and reduction of long-distance organ travel could contribute to improving their outcomes and overall utilization. Some authors have suggested that minimization of organ manipulation, rapid aortic cannulation and cold perfusion, topical cooling, and rapid hepatectomy have protective effects for older liver grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly grafts are more susceptible to ischemia/reperfusion injury because of hemodynamic instability. 13 Shorter cold ischemia time and reduction of long-distance organ travel could contribute to improving their outcomes and overall utilization. Some authors have suggested that minimization of organ manipulation, rapid aortic cannulation and cold perfusion, topical cooling, and rapid hepatectomy have protective effects for older liver grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The Celsior solution is more used than the UW and requires higher amounts. In situ flushing at cross-clamp is most commonly done through the aorta only, but a considerable number of centres flush the liver in situ also through the portal vein, reflecting probably the increasing amount of marginal livers utilized and the need to optimize flushing and preservation by combined arterial and portal perfusion as reported in the literature [10]. The method of washing the graft at back table is characterized by a wide variety of approaches, and most of the surgeons (78%) are in accordance with flushing the biliary tree in order to better preserve its integrity [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the SAP group, 5 cases required re-LT (< 30 d). Patient and graft survival rates were higher in the MDP (100% in both cases) than in the SAP group (68% and 58%, respectively) so that the study was stopped [70] .…”
Section: Retrieval Techniquesmentioning
confidence: 97%